Transformasi Karakteristik Arsitektur Modern Pada Fasad Porola Grand Renggali Hotel Takengon - Siska; Dafrina, A; Andriani, D (Cered Indonesia Institute, 2025)
Takengon City is a city in Aceh Province, which is located in the Gayo highlands, Central Aceh. The city of Takengon is known for its natural beauty, Lut Tawar Lake, and the richness of Gayo culture, including its superior coffee production. The development of tourism in the Takengon area, Central Aceh has also encouraged the growth of supporting infrastructure, including the hotel sector. There are many accommodation or hotel buildings in Central Aceh, one of the properties that stands out is the Portola Grand Renggali Hotel Takengon. Infrastructure such as hotels continues to develop with the times. including the Portola Grand Renggali Hotel Takengon which is known to have undergone a transformation process. The use of form follows function theory, which states that the form of a building is based on its function, to analyze the transformation of hotel architecture through facade elements. likely influenced by function, needs, or user expectations. In addition, the principle